Internet Pricing on Bandwidth Function Diminished With Increasing Bandwidth Utility Function - Indrawati Indrawati; Irmeilyana Irmeilyana; Fitri Maya Puspita; Oky Sanjaya (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
In this paper we analyze the internet pricing schemes based on bandwidth function diminished with increasing bandwidth utility function with 3 pricing strategies for homogeneous and heterogeneous consumer. The new proposed pricing schemes with this utility function will give the information to the internet service providers (ISP) in maximizing profits and provide better service quality for users. The Models on every type of consumer are applied to the data traffic in Palembang local server. LINGO 11.0 is used to compute the nonlinear programming problem to get the optimal solution. The results showed that for each case based on 3-pricing scheme, ISPs get better profit by choosing all three schemes in consumers type of homogenous case while for heterogeneous cases on willingness to pay and based on demand of the consumers, ISPs can select flat fee scheme to gain higher profit rather than those two other schemes.